Efektivitas Pelaksanaan Pelayanan Pengaduan Masyarakat Berbasis E-Government - Mahendra, Gerry Katon; Pribadi, Ulung (Journal of Governance and Public Policy, 2014)
Public complaints service todayâs has become part ofÂ  the efforts to improve public services in Indonesia. Government,both central and local levels is appropriate to give special attention to the improvement ofÂ  service quality ofÂ  publiccomplaints. The governmentâs attention can be achieved either by continuously innovate to create public complaintsservice that is not only easily accessible by the public, butÂ  also can be received and respondedÂ  to effectively by localgovernment. Yogyakarta Cityâs Government innovates by providing the services ofÂ  public complaints were based oninformation technology and communication (e-government). Innovations made by the government ofÂ  Yogyakar ta isexpected to provide ease ofÂ  access for the public and can be input which should be followed up effectively by thegovernment ofÂ  the city ofÂ  Yogyakarta so as to create improved quality ofÂ  public services in general in the future.